Effects of different bypass surgeries on LSA revascularization in patients with left subclavian occlusion. (26th July 2022) - Li, Da; Zeng, Xiangguo; Wang, Jiarong; Yuan, Ding; Zheng, Tinghui
Abstract: Introduction: Left subclavian artery (LSA) bypass surgery is mainly carried out for patients with severe left subclavian occlusion. This article aimed to evaluate the hemodynamic effects of different surgical bypass modes on LSA revascularization. Methods: Three‐dimensional models of the aorta were reconstructed from CTA images of a patient with LSA occlusion, a patient with type B aortic dissection with LSA coverage during thoracic endovascular aortic repair, and a healthy 74‐year‐old man, resulting in six modes for each person: healthy LSA mode, LSA occlusion mode and four bypass modes. Hemodynamic parameters, including flow field, flow distribution, pressure gradient, and wall shear stress, were calculated using computational fluid dynamics. Results: After LSA bypass surgery, distal LSA blood flow resulting from left common carotid artery (LCCA) to distal LSA bypass was 100% of that in the healthy mode, while the other modes yielded flows at least 91%. Moreover, reversed flow only completely disappeared with LCCA to distal LSA bypass, whereas reverse flow was observed in the other three modes in early systole. Conclusion: Left common carotid artery to distal LSA bypass can effectively reduce reverse blood flow in the left vertebral artery, and it is a feasible, effective, and safe option for LSA revascularization in patients with left subclavian occlusion. Abstract : Different LSA bypass modes showed different hemodynamic characteristics in arteries, which may lead to a complicated prognosis in patients with LSA occlusion. Through CFD simulation, this article found that the LCCA‐DLSA bypass mode had the best hemodynamic environment in LSA, LCA and LVA, indicating that LCCA‐DLSA bypass mode might be a better choice for patients with LSA occlusion.